FAKTOR-FAKTOR YANG MEMPENGARUHI SISTEM INFORMASI AKUNTANSI (Studi Pada Perusahaan Food and Beverage Yang Terdaftar di Bursa Efek Indonesia) - Diana Amalia; Maslichah Maslichah; Afifudin Afifudin (Universitas Islam Malang, 2021)
This study aims to determine the factors that affect the accounting information system. The case study in this research is the Food and Beverage Companies Listed on the Indonesia Stock Exchange). The independent variables in this study are the influence of user involvement, training and education, personal technical ability, top management support, and accounting information systems as the dependent variable. Sampling in this study using purposive sampling method. The test used in this research is multiple linear regression test. The sample obtained in this study were 30 respondents. The results of this study are the user involvement variable partially has a significant positive effect on accounting information systems. The variables of training and education partially have a significant positive effect on accounting information systems. The personal ability variable partially has a significant positive effect on the accounting information system. The top management support variable partially has a significant positive effect on the accounting information system.Keywords: Information Users, Training and Education, personal skills, management, accounting information systems.